2009
DOI: 10.1590/s0047-20852009000100009
|View full text |Cite
|
Sign up to set email alerts
|

Imunologia do transtorno bipolar

Abstract: Palavras-chaveTranstorno bipolar, imunologia, citocinas, quimiocinas, interleucinas, interferon e fator de necrose tumoral-α. rEsumo objetivo: Pesquisas recentes têm implicado fatores imunes na patogênese de diversos transtornos neuropsiquiátricos. O objetivo do presente trabalho é revisar os trabalhos que investigaram a associação entre transtorno bipolar e alterações em parâmetros imunes. métodos: Artigos que incluíam as palavras-chave: "bipolar disorder", "mania", "immunology", "cytokines", "chemokines", "i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
1
0
3
Order By: Relevance
“…The patient in this case had acceptable oral hygiene, but some systemic conditions, such as being under treatment for psychic illness (bipolarity) for 12 years. With the reported habits, such as chronic smoking in addition to the regular use of alcoholic beverages and marijuana, being decisive to understand the greater aggressiveness and speed in the progression of the periodontal clinical condition, it is observed in the literature that bipolarity is capable of generating an increase in the production of pro-inflammatory cytokines, which could lead to an increase in the chance of developing periodontal diseases (13). It has been reported that smoking alters the immune response and causes cytotoxicity in the periodontal tissues in addition to modifying the oral microbiota, facilitating…”
Section: Discussionmentioning
confidence: 99%
“…The patient in this case had acceptable oral hygiene, but some systemic conditions, such as being under treatment for psychic illness (bipolarity) for 12 years. With the reported habits, such as chronic smoking in addition to the regular use of alcoholic beverages and marijuana, being decisive to understand the greater aggressiveness and speed in the progression of the periodontal clinical condition, it is observed in the literature that bipolarity is capable of generating an increase in the production of pro-inflammatory cytokines, which could lead to an increase in the chance of developing periodontal diseases (13). It has been reported that smoking alters the immune response and causes cytotoxicity in the periodontal tissues in addition to modifying the oral microbiota, facilitating…”
Section: Discussionmentioning
confidence: 99%
“…Outros achados relevantes sugerem aumento nos níveis de anticorpos circulantes em associação a infecções virais, como herpes, Borna e parvovírus B19 [96][97][98][99] . Esses dados, de uma maneira ou outra, evidenciam a grande ligação entre o sistema imunológico e as vias fisiopatológicas do transtorno bipolar.…”
Section: Mediadores Inflamatóriosunclassified
“…Nas últimas décadas, com a demonstração do papel das citocinas em processos neurais como plasticidade sináptica, o número de pesquisas a respeito do envolvimento dessas substâncias no TB tem aumentado e vários autores apontam uma disfunção imune como um dos componentes etiológicos desse transtorno 11 .…”
Section: Introductionunclassified